Artificial roughness standard for open channels: abstract - Robinson, A. R. (August Robert), 1921-, author; Colorado A & M College, publisher (Colorado State University. Libraries, 1952)
There are two principle equations, which are used in computing discharges in open channels. These are: (1) Q = CA RS (Chezy), (2) Q = (1.486/n)AR2/3 S1/2 (Manning). The resistance coefficients C and n are assumed to be constant for a particular location. Previous investigations have shown that these coefficients may vary as much as 100 percent for the same section. A similar situation existed for pipes until a new method was devised for finding the resistance coefficient by using an artificial roughness standard and considering the magnitude of the Reynolds number. An artificial standard for the roughness, which exists in an open channel, is proposed. A design for the roughness is presented and this roughness tested in a range of conditions where the resistance to flow is due solely to the roughness.
CER47-52AAR40.
Presented before the Engineering Section, Colorado-Wyoming Academy of Science, Boulder, Colorado, May 2, 1952.
Keywords: Irrigation